2017
DOI: 10.7150/jca.19631
|View full text |Cite
|
Sign up to set email alerts
|

Loss of β-arrestin-2 and Activation of CXCR2 Correlate with Lymph Node Metastasis in Non-small Cell Lung Cancer

Abstract: Background: Although β-arrestin-2 (β-arr2) and CXCR2 have been shown to affect various malignant tumors, their exact roles in lung cancer remain unclear. We investigated expression of β-arr2 and CXCR2 in patients with non-small cell lung cancer (NSCLC) and their correlation with lymph node metastasis and prognosis.Methods: We reviewed medical records of 136 patients with NSCLC who underwent surgical resection, and assessed their specimens immunohistochemically for expression of β-arr2 and CXCR2 in primary tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Also, high expression of CXCR2 was associated with Dukes stage, tumor invasion and liver metastasis in colorectal cancer patients [21]. As for NSCLC, CXCR2 is highly expressed in primary tumors and metastatic lymph nodes of NSCLC, and the activation of CXCR2 promotes lymph node metastasis in NSCLC patients [17]. In accordance with the previous evidences, we observed that CXCR2 expression was higher in tumor tissues compared with paired adjacent tissues of SCLC.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Also, high expression of CXCR2 was associated with Dukes stage, tumor invasion and liver metastasis in colorectal cancer patients [21]. As for NSCLC, CXCR2 is highly expressed in primary tumors and metastatic lymph nodes of NSCLC, and the activation of CXCR2 promotes lymph node metastasis in NSCLC patients [17]. In accordance with the previous evidences, we observed that CXCR2 expression was higher in tumor tissues compared with paired adjacent tissues of SCLC.…”
Section: Discussionsupporting
confidence: 86%
“…As for NSCLC, the implication of CXCR2 is rarely reported, and only one study exhibits that CXCR2 is correlated with lymph node metastasis in NSCLC patients [17]. Besides, our preliminary study discovered that CXCR2 was overexpressed in both tumor tissues and cell lines of NSCLC, which promotes NSCLC cell proliferation.…”
Section: Introductionmentioning
confidence: 73%
“…Although β-arr1 and β-arr2 show high degree of sequence and structural similarity and functional overlap (Srivastava et al., 2015), emerging evidences establish an involvement of β-arr2 in cancer growth and progression, with contradictory results. Previous studies demonstrated that β-arr2 depletion promoted tumor growth and angiogenesis in a murine model of lung cancer (Raghuwanshi et al., 2008) and that low expression of β-arr2 is significantly associated with aggressive pathologic features and is predictive of poor patient prognosis, as observed in lung and hepatocellular carcinoma (Sun et al., 2016; Cong et al., 2017). In prostate cancer, β-arr2 inhibits cell viability and proliferation by downregulation of FOXO1 and represses AR signaling, and AR expression/activity negatively correlates with β-arr2 expression (Lakshmikanthan et al., 2009; Duan et al., 2015).…”
Section: Role Of β-Arr2 In Cancer Progressionmentioning
confidence: 99%
“…CXCR2, the co-receptor of IL-8 and CXCL1, is an important therapeutic target in a number of solid tumor types, including lung, breast, prostate, ovarian, colorectal and liver cancer ( 50 55 ). Xu et al ( 56 ) revealed that CXCR2 may promote breast cancer metastasis and chemoresistance via the suppression of AKT serine/threonine kinase 1 and activation of cyclooxygenase 2.…”
Section: Discussionmentioning
confidence: 99%